The effect of work-related sustained trapezius muscle activity on the development of neck and shoulder pain among young adults - Therese Nordberg Hanvold; Morten Wærsted; Anne Marit Mengshoel; Espen Bjertness; Hein Stigum; Jos Twisk; Kaj Bo Veiersted (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: This study aimed to evaluate if sustained trapezius muscle activity predicts neck and shoulder pain over a 2.5-year period. METHODS: Forty young adults (15 hairdressers, 14 electricians, 5 students and 6 with various work) were followed during their first years of working life. Self-reported neck and shoulder pain during the last four weeks was assessed seven times over the observational period. Upper-trapezius muscle activity was measured during a full working day by bilateral surface electromyography (EMG) at baseline (winter 2006/7). Sustained trapezius muscle activity was defined as continuous muscle activity with amplitude >0.5% EMGmax lasting >4 minutes. The relative time of sustained muscle activity during the working day was calculated and further classified into low (0-29%), moderate (30-49%) and high (50-100%) level groups. RESULTS: Generalized estimating equations (GEE), adjusted for time, gender, mechanical workload, control-over-work intensity, physical activity, tobacco use, and prior neck and shoulder pain, showed that participants with a high level of sustained muscle activity had a rate of neck and shoulder pain three times higher than the low level group during a 2.5-year period. The association was strongest at the same time and shortly after the EMG measurement, indicating a time-lag of ≤6 months. CONCLUSION: The results support the hypothesis that sustained trapezius muscle activity is associated with neck and shoulder pain. This association was strongest analyzing cross-sectional and short-term effects.